2017
DOI: 10.1038/ncomms16114
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of FBXL5-mediated cellular iron homeostasis in maintenance of hematopoietic stem cells

Abstract: Hematopoietic stem cells (HSCs) are maintained in a hypoxic niche to limit oxidative stress. Although iron elicits oxidative stress, the importance of iron homeostasis in HSCs has been unknown. Here we show that iron regulation by the F-box protein FBXL5 is required for HSC self-renewal. Conditional deletion of Fbxl5 in mouse HSCs results in cellular iron overload and a reduced cell number. Bone marrow transplantation reveals that FBXL5-deficient HSCs are unable to reconstitute the hematopoietic system of irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…Previous studies have indicated that iron homeostasis is crucial for various kinds of stem cell. For example, iron overload can impact the self‐renewal and function of hematopoietic stem cells and progenitor cells [23,24], whereas iron deficiency impairs the pluripotency of hESCs/hiPSCs [15]. Besides, it has been reported that iron deficiency inhibited the expression of stemness markers and spherogenesis in cancer stem cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that iron homeostasis is crucial for various kinds of stem cell. For example, iron overload can impact the self‐renewal and function of hematopoietic stem cells and progenitor cells [23,24], whereas iron deficiency impairs the pluripotency of hESCs/hiPSCs [15]. Besides, it has been reported that iron deficiency inhibited the expression of stemness markers and spherogenesis in cancer stem cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has shown that iron homeostasis is critical for stem cells. For example, iron overload can affect the self‐renewal, frequency, and functioning of hematopoietic stem and progenitor cells . Thus far, little is known regarding the role of iron homeostasis in maintaining the biological property of PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Several pathways including Wnt-β catenin, PIK3CA/AKT/PTEN, and NF-κB, have been postulated as targets for NSAIDs [54]. FBXL5 has previously been interpreted as oncogene whilst its association in iron regulation is required for HSC self-renewal [52]. In CRC progression, FBXL5 has shown to induce cell proliferation, growth, tumorigenesis and inhibit cell apoptosis by modulating PTEN/PI3K/AKT signalling and its overexpression resulted in high tumour formation ability [24,27].…”
Section: Discussionmentioning
confidence: 99%
“…When used in FBXL5-KO-cells, AM404 showed sensitivity and further additive effect in preventing cells invasion suggesting AM404 as a new compound to target FBXL5 in blocking CRC cell migration. We currently do not have an in vivo intestinal/colon model that implicit FBXL5 as a potential therapeutic target for cancer stem cells, although an essential role of FBXL5-mediated cellular iron homeostasis in the maintenance of hematopoietic stem cells has already been reported [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation